Characterization of vacuum-packed sterilized biko as disaster food - Lim, Jadice J.
In the Philippines, biko is one of the famous rice cakes eaten during festivals and special occasions. A prototype vacuum-packed sterilized biko obtained from a previous study was characterized for its suitability as a disaster food by conducting focus group discussions, consumer acceptance tests, and physico-chemical tests. The results of the focus group discussion showed that the prototype was fit for a disaster food as it is culturally acceptable, has long shelf-life, and requires no preparation. Nine point hedonic scale consumer acceptance test results indicate that the 4- and 8- week old prototypes obtained scores ranging from ―neither like nor dislike‖ (week 4 color, appearance, texture and overall acceptability) to ―like moderately‖ (week 8 sweetness and taste) and were significantly less acceptable compared to a commercial sample for color, appearance, texture, and overall acceptability. Physico-chemical tests comparing week 4 and 8 prototypes indicate no significant difference in pH (5.5233 vs. 5.500) and lower water activity (0.8133 vs. 0.8660) and L- (43.5067 vs. 45.3500), a- (8.9933 vs. 10.4300), b- (31.6600 vs. 33.4933) color for week 4. The study concludes that the final prototype of the vacuum-packed sterilized biko was deemed suitable as a disaster food by those affected by natural disasters even though the panellist from the consumer acceptance test found the commercially-available sample more acceptable.